Przeciwdziałanie dyskryminacji przedsiębiorstw ubezpieczeniowych w świetle dyrektyw ubezpieczeniowych Unii Europejskiej - Baranowska-Zając, Wioleta (Kwartalnik Prawa Publicznego, 2012)
The prohibition of discrimination belongs to a group of basic principles of the European Union legislation. The prohibition of discrimination on grounds of nationality is provided in the article 18 of the Treaty on the functioning of the European Union (TFEU). That prohibition is a general prohibition and in relation with special prohibitions of discrimination has a subsidiary character. Special prohibitions of discrimination are provided, for example, in article 49 TFEU, that establishes a freedom of establishment, and in article 56 TFEU, that refers to a freedom to provide services. There are several possible forms of discrimination that could take place in the insurance sector and one of them is a discrimination against insurance undertakings. Insurance undertakings that provide insurance services on the internal market of the European Union either on the basis of the freedom of establishment or on the freedom to provide services could be discriminated by both Member States and the institutions of the European Union. The former insurance directives contained and the directive 2009/ /138/EC of the European Parliament and of the Council of 25.11.2009 on the taking – up and pursuit of the business of insurance and reinsurance, that is now in force, contains many regulations that cause or that may cause discrimination against insurance undertakings on the internal market and other restrictions of freedom of establishment and freedom to provide services.